PENGARUH DIGITALISASI ARSIP DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR PUSAT PT. BANK SULUTGO - Djawa, Djibrael; Pomantow, Willem Gilbert; Kalalo, Mayriana Omega (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2025)
The problems raised in this article are the factors that effect employee performance and work culture, especially in the field of archive digitalization. While the research goal to be achieve is to find out the Effect of archive Digitalization and Work Cultureon employee Performance at the Head Office of PT Bank SulutGo as well as knowing the process of Digitalization of Archives at the Head Office of PT Bank SulutGo bank. The analysis tools used in this research is descriptive statistical analysis, namely by conducting a statistical calculation. From the result of the analysis in the study obtained the value of the simultaneous correlation coefficient r = 0.752 or the value is positive, than thjis shows that the digitalization of Archieve and Work Culture has a strong significant relationship with the improvement of employee performance at the Head Office of PT Bank SulutGo Bank. While the determination coefficient value shows that the improvement 43.4% is effected by the digilization of Archives and work culture. At the same time, while the remaining 56.6% is effected by the other factor. The result of the analysis show that the digitalization of archives and work culture have a significant influence on the improvement of employee performance at the Head Office of PT SulutGo Bank.